Effects of agroforestry on grain yield of maize (Zea mays L.)—A global meta-analysis - Baier, Clara; Gross, Arthur; Thevs, Niels; Glaser, Bruno (Frontiers in Sustainable Food Systems, 2023)
Maize cropping systems, the world's most important cropping systems in terms of production volume, are responsible for many environmental problems, such as soil degradation and erosion. This calls for sustainable practises that enable environment-friendly production while generating sufficient output, as farmers and consumers worldwide depend on adequate yields. Agroforestry can offer solutions to both of these pressing concerns—food insecurity and adverse environmental impacts of intensive maize cultivation. This meta-analysis investigated the effects of agroforestry on maize (Zea mays L.) grain yield under different environmental and management regimes on a global scale. It is based on 1,215 pairwise data entries from 95 peer-reviewed studies. Overall, agroforestry increased median maize yields by 0.24 Mg ha−1 (7%) compared to tree/hedgerow-free maize monocultures. In subtropical and tropical regions, the median yield increment under agroforestry was 0.30 Mg ha−1 (+16%), and the best results were achieved using broadleaved trees (+0.42 Mg ha−1, +53%), especially N-fixing tree species (+0.56 Mg ha−1, +60%). Maize yields responded very well to the addition of tree prunings to the soil of the maize crop (+0.48 Mg ha−1, +24%). Rotating maize with other crops was beneficial if the intermediate crop is able to fix atmospheric N (+0.28 Mg ha−1, +13%). We found that hedgerow planting densities of at least 5,000 woody perennials ha−1 are required for the positive impacts of agroforestry on maize yields to take effect, and these effects increased with both tree age (+1.17 Mg ha−1, +48% under trees 11–15 years of age) and time under agroforestry (+0.85 Mg ha−1, 81% in response to >15 continuous maize seasons under agroforestry). In addition, they were particularly pronounced on sandy soils (+0.46 Mg ha−1, +23%), moderately acidic soils of pH 5–6 (+0.67 Mg ha−1, +35%), soils with <0.5 g kg−1 N (+1.19 Mg ha−1, +81%), soils with a plant-available water holding capacity <10 mm dm−1 (+1.10 Mg ha−1, +44%), and hyper-arid conditions (+0.60 Mg ha−1, +35%). These findings prove that if designed with due regard for local conditions and crop/tree species characteristics, agroforestry can be a powerful tool to increase food security and the sustainability of maize production systems.